2010
DOI: 10.1136/bcr.05.2009.1891
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal food impaction in achalasia treated with Coca-Cola and nifedipine

Abstract: Achalasia is characterised by the loss of peristaltic movement in the distal oesophagus and failure of the lower oesophageal sphincter relaxation, which results in impaired oesophageal emptying. We report a case of a 92-year-old frail woman with a history of achalasia, who presented with acute oesophageal obstruction due to impaction of a large amount of food material. She was treated successfully with nifedipine, in combination with Coca-Cola (original product, not sugar free), so avoiding the risks associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Tedavide en temel ve öncelikli girişim derhal havayolunun endotrakeal entübasyon ile güvence altına alınması ve takiben de nazo-özofageal sonda yerleştirerek özofagus dekompresyonun sağlan-masıdır. Kimi zaman özofagusun aşırı dilate ve tamamen dolu olduğu durumlarda tekrarlayan entübasyon ve dekompresyona gerek olabilmekte ve böylece hasta artmış aspirasyon, travma ve perforasyon riski ile karşı karşıya kalabilmektedir [14] . Akalazyanın uzun dönem tedavisinde ise pnömatik dilatasyon, endoskopik botulismus toksin (BOTOX) enjeksiyonu gibi endoskopik yöntemler ile Heller myotomi ve özafajektomi gibi cerrahi prosedürler uygulanmaktadır [15] .…”
Section: Discussionunclassified
“…Tedavide en temel ve öncelikli girişim derhal havayolunun endotrakeal entübasyon ile güvence altına alınması ve takiben de nazo-özofageal sonda yerleştirerek özofagus dekompresyonun sağlan-masıdır. Kimi zaman özofagusun aşırı dilate ve tamamen dolu olduğu durumlarda tekrarlayan entübasyon ve dekompresyona gerek olabilmekte ve böylece hasta artmış aspirasyon, travma ve perforasyon riski ile karşı karşıya kalabilmektedir [14] . Akalazyanın uzun dönem tedavisinde ise pnömatik dilatasyon, endoskopik botulismus toksin (BOTOX) enjeksiyonu gibi endoskopik yöntemler ile Heller myotomi ve özafajektomi gibi cerrahi prosedürler uygulanmaktadır [15] .…”
Section: Discussionunclassified
“…We hypothesised that cola would be successful in 50% of patients, based on previous non-randomised studies on cola treatment reporting food bolus passage in 59-100% of instances. [12][13][14][15] We estimated a 10% chance of spontaneous passage in the control group, simply awaiting emergent endoscopy. Assuming a power of 0.8 and a 5% significance level, a sample size of 40 patients was required.…”
Section: Methodsmentioning
confidence: 99%
“…Previous small studies have reported success rates of cola ingestion doi: 10.1136/bmj-2023-077294 | BmJ 2023;383:e077294 | the bmj ranging from 59% to 100%, with no reported short term adverse events. [12][13][14][15] Carbon dioxide is thought to be responsible for the mechanism of clearing impaction, or disimpaction, by effervescent agents. However, the exact mechanism is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Those who search online for remedies for stuck food will find that the internet is replete with advice for cola use. Cola has also been advocated as a safe treatment for patients in whom endoscopic removal of a food bolus is judged to be too risky [17] , [18] . Despite its popularity, there is minimal evidence surrounding cola’s use in removing food boluses.…”
Section: Introductionmentioning
confidence: 99%